Ice nucleation activity identified in some phytopathogenic Fusarium species - Richard, C.; Martin, J.-G.; Pouleur, S. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1996)
In order to know which species of Fusarium are ice nucleating and to determine the factors affecting their pathogenicity, ice nucleation activity (INA) was examined in Fusarium oxysporum, F. sporotrichioides, and F. tricinctum. Positive controls (lna+) used were F. acuminatum and F. avenaceum. The test for fungal INA was done with a simple and rapid tube nucleation assay. Twelve out of the 42 F. oxysporum isolates, and 8 out of 14 F. tricinctum isolates were lna+. No INA was detected in F sporotrichioides. In this test the threshold freezing temperature tended to increase with culture age, reaching a peak of -1°C in a few samples, which is as high as the warmest INA reported for bacteria, and higher than the INA detected in pure cultures of free-living fungi, lichen fungi, lichen algae and cyanobacteria. This is the first report of INA for F oxysporum.